Depressive, anxiety, and burnout symptoms on health care personnel at a month after COVID-19 outbreak in Indonesia - Deni Kurniadi Sunjaya; Dewi Marhaeni Diah Herawati; Adiatma Y. M. Siregar (BMC, 2021)
Abstract Background Health care personnel (HCP) who demonstrated close contact with Corona virus disease (COVID-19) patients might experience a higher risk of infection and psychological problems. This study aims to explore depressive, anxiety, and burnout symptoms among HCP with a higher risk for psychological trauma. Methods This study was a cross-sectional study using secondary data from an online assessment, which was conducted 1 month after the COVID-19 outbreak. A total of 544 respondents from 21 provinces in Indonesia were included. Data on depressive, anxiety, and burnout symptoms were transformed first using the Rasch model and then categorized. Data from HCP in the higher risk group and the lower risk group were analyzed. Results A higher percentage of HCP experiencing depressive symptoms (22.8%), anxiety (28.1%), and burnout (26.8%) are found in the higher risk group. The chance for the higher risk group's HCP to present with moderate and severe depressive symptoms, anxiety, and burnout are: 5.28 (Confidence interval (CI): 2.01-13.89; p < 0.05), 1.36 (CI: 0.09-1.96; p >  0.05), and 3.92 (CI: 2.08-7.40; p < 0.05) times higher, respectively. The probability for patient-induced burnout is 2.13 (CI: 1.51-3.007; p < 0.05) times higher and highest among the other burn out dimensions. The depressive symptoms complained were similar between groups: loneliness, sleep disturbances, difficulty concentrating, and inability to initiate activities. Loneliness demonstrates the highest logit value among the symptoms. Conclusions HCP with direct contact and responsibility to treat COVID-19 patients exhibit a higher risk to experience depressive symptoms and burnout. Communication with peers and staying in contact with family needs to be encouraged. Psychological well-being should be considered for high-risk HCP. Incentive or insurance guaranteed by the government or institution is essential as a reward and compensation during this period.